2016
DOI: 10.1007/s10151-016-1543-2
|View full text |Cite
|
Sign up to set email alerts
|

Surface anatomical landmarks for the location of posterior sacral foramina in sacral nerve stimulation

Abstract: We found that the distance between sacral foramina and MSC is relatively constant while the distance between foramina and the relations between foramina and PSIS is highly variable. Detailed knowledge of the anatomy may facilitate electrode placement and is complementary to the regular use of fluoroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
8
0
2
Order By: Relevance
“…Although these bony landmarks can usually be identified easily, the operator's experience is essential for correct positioning, as the orientation of the sacral bone and the amount of subcutaneous fatty tissue varies among individuals. Indeed, cadaver studies have shown large variability in size and distance of bony sacral landmarks: e.g., the distance from the upper part of the S3 foramen to the tip of the coccyx has a mean of 9.26 cm, but in only 18 cadavers the range was 3.4 cm . If one relies on bony landmarks alone, lead placement could easily be at S2 or S4 in some of these patients.…”
Section: Resultsmentioning
confidence: 99%
“…Although these bony landmarks can usually be identified easily, the operator's experience is essential for correct positioning, as the orientation of the sacral bone and the amount of subcutaneous fatty tissue varies among individuals. Indeed, cadaver studies have shown large variability in size and distance of bony sacral landmarks: e.g., the distance from the upper part of the S3 foramen to the tip of the coccyx has a mean of 9.26 cm, but in only 18 cadavers the range was 3.4 cm . If one relies on bony landmarks alone, lead placement could easily be at S2 or S4 in some of these patients.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, one may speculate that this anatomical alteration may not be clinically relevant. In a study by Povo et al,20 human cadavers were dissected to define landmarks for optimal SNM lead placement, and no exostosis was described [13]. The age of the cadavers was not mentioned in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Harman demonstrated in 1899, in a series of six fetal cadavers, the intra‐ and inter‐individual variety of the origin of sacral nerves, pelvic plexus and pelvic splanchnic nerves . Povo and colleagues noted high variability in the distance between S3 and S4 on both sides and in the distance between S2 and S3 in adults . Although this was demonstrated in human cadavers, one could assume similarities to pigs.…”
Section: Discussionmentioning
confidence: 99%